Engineering application of desulfurization and denitrification comprehensive purification technology for activated coke. Issue 5 (12th April 2021) - Wu, Zihua; Li, Dandan; Chen, Hao; Zhang, Shule; Zhong, Qin
Abstract: This article discusses the desulfurization and denitrification integrated purification technology for activated coke. This technology has been widely used in globally due to its ability to simultaneously remove NO x, SO2, dioxin, and dust from the flue gas. The approach discussed adopts a cross‐flow method in which the activated coke flows from the top to the bottom in the adsorption tower, and the flue gas passes through the activated coke bed horizontally from the side. To create a more economically appealing solution, the waste heat recovery system is optimized and a regeneration gas processing system is added to recycle the gas with a high concentration of SO2 . In this process, first desulfurization and then denitrification. The denitrification process is performed by selective catalytic reduction of NO x with NH3 reaction (NH3 ‐SCR). The results show that under the flue gas condition (NO x = 300 mg/Nm 3 and SO2 = 200 mg/Nm 3 ), SO2 is almost completely removed and the NO x removal efficiency is greater than 80%. After SO2 adsorption, the activated coke can be regenerated in a regeneration furnace at 400–450°C and the highly concentrated SO2 produced during the regeneration process can be further used for the production of ammonium sulfate. The purpose of the regeneration reaction of activated coke is to reactivate and recover the activated coke. Finally, the cost analysis results of the system show that the desulfurization and denitrification integrated purification technology for activated coke has excellent economic benefits.